Application, involvement, and relevance of good corporate governance practice principles in sports entities - Ribeiro, Henrique César Melo; Costa, Benny Kramer (Revista de Administração da UFSM, 2018)
The objective of this study was to investigate the application, involvement, and relevance of principles of good corporate governance practices in sports entities. Eight sporting entities were studied, using the multiple case study method. For the data treatment, intra-case and inter-case analyses were used. We observed that in all the sports entities analyzed, the principles of good corporate governance practices have relevance and involvement, and are mainly tied to transparency and accountability. This information contributes to the understanding that principles of corporate governance are essential for any organization, including sports entities. This proves that corporate governance is not just another elementary and immature theme in sporting entities. We concluded that these principles are preponderant for the sports entities, contributing to their modernization and their professionalism in the world sports scenario.